Parques nacionais e revolução social - Márcia Dieguez Leuzinger (Sustentabilidade em Debate, 2013)
WAKILD, Emily. Revolutionary parks: conservation, social justice and Mexico’s national park’s, 1910-1940. Tucson: The University of Arizona Press, 2011. Latin American Landscapes Series. Bibliografia, índice remissivo, mapas, fotos. ISBN: 9780816529575.